Effect of spore concentration of Alternaria tenuissima on germination and development of germ tubes on host and nonhost - B. PRITHIVIRAI; B.K. SARMA, S.K. SINGH, U.P. SINGH, L. TULI, (Indian Phytopathology, 2002)
Effect of spore concentration on germination and development of germ tubes of Alternaria tenuissima on various substrates (glass slides, leaves of susceptible (cv. Bahar) and resistant (cv. MA128-2) pigeon pea [Cajanus cajan]) was observed at different intervals (6 h). Various substrates significantly affected conidial germination and development of A. tenuissima at 6 h intervals. There was no germination on leaves of resistant pigeon pea at 16 x 106 spores/ml. At the same concentration, germination was very poor on glass slides and on susceptible pigeon pea leaves after 24 h. Length of germ tubes also increased as did germination with decreasing spore concentration. Germ tube development was faster at lower concentration. The rate of germ tube development was very slow on resistant leaves as compared to glass slides and susceptible leaves. Higher spore concentrations (16 x 106 and 32 x 105 spores/ml) produced disease symptoms on susceptible pigeon pea plants within 7 and 8 days, respectively, with 100% disease intensity. Drops containing 512 x 10 spores/ml failed to produce disease symptoms within 15 days in cv. Bahar.